Balancing Cybersecurity and Fundamental Rights: The Responsibility of States to Address Cyber Threats - Nshimiyimana, Francois Regis (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2025)
The rise of cyber threats poses significant challenges to states, necessitating robust cybersecurity measures. However, these measures often risk infringing upon fundamental rights such as privacy, freedom of expression, and access to information. This paper explores the delicate balance between ensuring cybersecurity and protecting individual rights, emphasizing the responsibility of states to address these challenges. The study examines legal frameworks and policies governing cybersecurity and fundamental freedoms using comparative legal methods. It reveals disparities in states' approaches, with some prioritizing security over rights while others strive for a balanced approach. The research emphasizes the importance of incorporating human rights considerations into cybersecurity policies. The conclusion emphasizes the need for a comprehensive approach involving government, business, and civil society partners in developing policies prioritizing security and safeguarding fundamental rights. This study is highly relevant because it provides crucial insights into the complex field of cybersecurity law and how it affects human rights. It also offers recommendations that will help policymakers effectively tackle these complex issues.